2007
DOI: 10.1208/pt0803075
|View full text |Cite
|
Sign up to set email alerts
|

Micromatricial metronidazole benzoate film as a local mucoadhesive delivery system for treatment of periodontal diseases

Abstract: The main objective of this study was to develop a local, oral mucoadhesive metronidazole benzoate (MET) delivery system that can be applied and removed by the patient for the treatment of periodontal diseases. Mucoadhesive micromatricial chitosan/poly(ε-caprolactone) (CH/PCL) films and chitosan films were prepared. Thermal behavior, morphology, and particle size measurements were used to evaluate the prepared films. The effect of different molar masses of CH and different ratios of medium Mwt molar mass chitos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 28 publications
(31 reference statements)
0
41
1
1
Order By: Relevance
“…Among antibiotics, MET is used in the oral cavity for treating infections by anaerobic bacteria associated with periodontal diseases due to its low minimum inhibitory concentration [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among antibiotics, MET is used in the oral cavity for treating infections by anaerobic bacteria associated with periodontal diseases due to its low minimum inhibitory concentration [5].…”
Section: Discussionmentioning
confidence: 99%
“…Among antibiotics, metronidazole (MET) is highly effective for the management of anaerobic infections, such as intraabdominal and gynecologic infections, septicemia, endocarditis, bone and joint infections, central nervous system infections, respiratory tract infections, skin and skin-structure infections. Moreover, MET is largely used for treating infections by anaerobic bacteria associated with periodontal diseases due to the low minimum inhibitory concentration it requires [5]. For treatment of mixed aerobic and anaerobic infections, metronidazole should be used in combination with other antibacterial agents that are appropriate for the treatment of the aerobic infection, because MET is ineffective against aerobic bacteria [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…A ratio of 1:0.625 for chitosan:PCL presented best tensile properties and slowest drug release. In vitro studies showed saliva concentrations of 5 to 15 mg/ml over 6 hours, which was within and above the MIC for metronidazole (El-Kamel et al, 2007). Recently Labib and coworkers developed films by solvent casting technique.…”
Section: Filmsmentioning
confidence: 89%
“…Different polymers such as polyethylene glycol [9,20], poly vinyl alcohol [4,24], polymethylmethacrylate [16],polysaccharides [6,11]. Other uses of nitroimidazole polymer complexes as delivery systems are reported in periodontal diseases [2,21], amebiasis [6,13,22], helicobector pylori [7], gentamycin [16], vaginitis [8], gastritis [10,12], sprays [19], liposomes [25].…”
Section: Discussionmentioning
confidence: 99%